Commodity Prices : Cyclical Weakness or Secular Decline? - Wickham, Peter (IMF Working Papers; Working Paper ;, 1994)
Primary commodities still account for the bulk of exports in many developing countries. However, real commodity prices have been declining almost continuously since the early 1980s and there is evidence of renewed weakness. The appropriate policy response to a terms of trade shock depends importantly on whether the shock is perceived to be temporary or permanent. Our results indicate that the recent weakness in commodity prices is mostly of a secular nature, stressing the need for commodity exporting countries to concentrate on export diversification and other structural policies. There is, however, scope for stabilization funds and the use of hedging strategies since the evidence also suggests commodity prices have become more volatile.